The Influence of Service Quality, Amenities, and Value on Customer Satisfaction and Customer Loyalty at Bobocabin Cikole Bandung - Danniella Nathannia Nimeesha; Ira Fachira (Global Writing Academica Researching and Publishing, 2025)
Although Indonesia's hotel industries have made an outstanding recovery, the developing glamping sector has specific challenges. These challenges include inadequate infrastructure and limited access to glamping locations, which hinder the ability to provide an exceptional customer experience. This study aims to address this issue by examining the impact of service quality, facilities, and value on customer satisfaction and loyalty at Bobocabin Cikole Bandung, with the goal to improve glamping experiences. The study utilizes a quantitative approach to examine the relationship between service quality, amenities, volume customer satisfaction, and loyalty. An online questionnaire is employed to collect data from 200 respondents. The data gathered is then analyzed using PLS-SEM to confirm relationships and generate actionable insights and recommendations. The findings indicate that service quality does not significantly impact customer satisfaction or loyalty. However, amenities and value significantly impact customer satisfaction. Customer satisfaction mediates the relationship between amenities, value, and loyalty, but not between service quality and loyalty. Glamping operators should improve amenities, value, and unique experiences to enhance customer satisfaction and loyalty. Further research should examine various glamping types, larger samples, and reasons for service quality’s limited impact. This study emphasizes the importance of amenities and perceived value for sustained success.